ChemInform Abstract: Reversible Storage of Lithium in Three‐Dimensional Macroporous Germanium. Issue 51 (23rd December 2014) - Jia, Haiping; Kloepsch, Richard; He, Xin; Badillo, Juan Pablo; Gao, Pengfei; Fromm, Olga; Placke, Tobias; Winter, Martin
Abstract Macroporous Ge with a hexagonal‐like morphology is prepared by magnesiothermic reduction of GeO2 (corundum boat, 5%H2/Ar, 650 °C, 7 h).